Capacitive Power Transfer Through Rotational and Sliding Bearings - Hagen, Skyler (My University, 2017)
Throughout the history of electrification, applications have existed for the transmission of electrical energy from stationary sources to moving loads. Electrical equipment which is expected to move along tracks, or in cyclical, pivoting, or rotational patterns of motion often requires externally-supplied electrical power to operate. Various techniques have been used with success in the past such as brushes with sliding contacts [1], cable connections (when practical), and various inductive and capacitive contactless power transfer strategies [2],[3],[4],[5]; however, each has its own limitations in longevity and/or complexity. Applications for power transfer to moving loads proliferate in the automotive and traction industries, as well as automation and manufacturing. Both of these categories have strict requirements on reliability. Failure in operation can be hazardous to human life and property in the case of transportation and heavy equipment traction. In the case of manufacturing, the reliability requirement is justified by the large opportunity cost incurred by machine down time. The following is a proposition for a technology which is well suited for many key modern applications. Using the nanofarad-scale capacitance already present in a variety of rotational and linear journal bearings, along with a simple soft-switching high frequency power converter circuit, power levels in the 102-103 watt range have successfully been transferred capacitively from stationary power sources to moving loads. This capacitive power transfer strategy opens up the opportunity for dual utilization of bearings, as mechanical support members and power transfer mechanisms. Background theory and experimental results are discussed for both rotary and linear power transfer through commercially available plain journal bearings. Power transfer at 600 watts is demonstrated through a pair of rotational hydrodynamic journal bearings; 111 watts through off-the-shelf linear plain bearings sliding on anodized aluminum shafting.